2014
DOI: 10.1111/jcmm.12461
|View full text |Cite
|
Sign up to set email alerts
|

Role of p38 MAPK in enhanced human cancer cells killing by the combination of aspirin and ABT‐737

Abstract: Regular use of aspirin after diagnosis is associated with longer survival among patients with mutated-PIK3CA colorectal cancer, but not among patients with wild-type PIK3CA cancer. In this study, we showed that clinically achievable concentrations of aspirin and ABT-737 in combination could induce a synergistic growth arrest in several human PIK3CA wild-type cancer cells. In addition, our results also demonstrated that long-term combination treatment with aspirin and ABT-737 could synergistically induce apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Furthermore, the ERK signaling pathway in addition to the p38 signaling pathway may regulate numerous factors that are associated with cancer progression and poor prognosis in NSCLC (31)(32)(33). The MMP family comprises 24 zincdependent endopeptidases, and serves important roles in tumor metastasis and MMP26 is associated with the invasion and metastasis of non-small cell lung cancer (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the ERK signaling pathway in addition to the p38 signaling pathway may regulate numerous factors that are associated with cancer progression and poor prognosis in NSCLC (31)(32)(33). The MMP family comprises 24 zincdependent endopeptidases, and serves important roles in tumor metastasis and MMP26 is associated with the invasion and metastasis of non-small cell lung cancer (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“… found that long‐term combination treatment with aspirin and a small‐molecule Bcl‐2/Bcl‐xL antagonist (ABT‐737) could synergistically induce apoptosis both in A549 and H1299 cell lines. Meanwhile, combination treatment with short‐term aspirin and the small‐molecule Bcl‐2/Bcl‐xL antagonist (ABT‐737) caused a greater autophagic response than that to either drug alone, and autophagy switched from a cytoprotective signal to a death‐promoting signal . P38 acts as the cellular switch between these two different cell death pathways (i.e., autophagy and apoptosis) induced by cotreatment with aspirin and ABT‐737 .…”
Section: Autophagy: Novel Applications Of Nsaidsmentioning
confidence: 99%
“…In 2016, the US Preventive Services Task Force recommended low‐dose aspirin for preventing colorectal cancer (CRC) in patients without a bleeding tendency . More recently, several novel studies have examined NSAIDs and cancer , and some researchers found that NSAIDs are closely related to autophagy, especially in hepatocellular carcinoma (HCC) , glioblastoma , neuroblastoma , acute leukemia , lung adenocarcinoma , oral cancer , breast cancer , ovarian cancer, colon cancer , bladder cancer, and gastric cancer . In this article, we will review the mechanisms underlying the actions of NSAIDs in autophagy (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…p38 MAPK (p38), one of three distinct families of MAPKs (ERK, JNK and p38 kinase), is a vital factor mediating ASA functions, such as ASA-induced anti-inflammatory and anticancer effects [10,11] . In addition, p38 activation is involved in the fibrosis of various organs.…”
Section: Introductionmentioning
confidence: 99%